2021
DOI: 10.1111/gcb.15589
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass (Halophila stipulacea) invasion enhances carbon sequestration in the Mediterranean Sea

Abstract: The introduction and establishment of exotic species often result in significant changes in recipient communities and their associated ecosystem services. However, usually the magnitude and direction of the changes are difficult to quantify because there is no pre‐introduction data. Specifically, little is known about the effect of marine exotic macrophytes on organic carbon sequestration and storage. Here, we combine dating sediment cores (210Pb) with sediment eDNA fingerprinting to reconstruct the chronology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 105 publications
1
21
0
Order By: Relevance
“…Moreover, our assessment does not consider the likely poleward migration of species, whether through natural propagation or assisted by human introductions. For instance, the occurrence of the exotic Halophila stipulacea from the Red Sea (T limit 38°C) in the Eastern Mediterranean may ensure continuity of ecological functions and services (Wesselmann et al, 2021) associated with seagrass habitats against the predicted loss of Posidonia oceanica (average T limit 28°C) with future warming (Jordà et al, 2012;Chefaoui et al, 2018). Moreover, the decadal time scales involved before seagrass reach T limit values even under the "business as usual" scenario, may allow adaptation, particularly so for the small, fast-growing species, such as Z. noltii or Halophila species (Duarte et al, 2018;Wesselmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our assessment does not consider the likely poleward migration of species, whether through natural propagation or assisted by human introductions. For instance, the occurrence of the exotic Halophila stipulacea from the Red Sea (T limit 38°C) in the Eastern Mediterranean may ensure continuity of ecological functions and services (Wesselmann et al, 2021) associated with seagrass habitats against the predicted loss of Posidonia oceanica (average T limit 28°C) with future warming (Jordà et al, 2012;Chefaoui et al, 2018). Moreover, the decadal time scales involved before seagrass reach T limit values even under the "business as usual" scenario, may allow adaptation, particularly so for the small, fast-growing species, such as Z. noltii or Halophila species (Duarte et al, 2018;Wesselmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The future expansion of H. stipulacea and the potential shift in the dominant flora in the Mediterranean (from P. oceanica to H. stipulacea and the native warm tolerant species C. nodosa) may have profound effects on seagrass ecosystem functioning. The ecological roles of P. oceanica and H. sipulacea are different as they have different evolutionary histories and H. stipulacea tends to colonize muddy estuarine waters and unstable environments (Wesselmann et al, 2021). The limited information available on the provision of ecosystem functions of H. stipulacea in the Mediterranean Sea indicates a similar carbon storage capacity of H. stipulacea and native seagrasses in the eastern Mediterranean (Wesselmann et al, 2021), although carbon stocks in that region ranks among the lowest across seagrass meadows (Fourqurean et al, 2012;Duarte et al, 2013;Mazarrasa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The ecological roles of P. oceanica and H. sipulacea are different as they have different evolutionary histories and H. stipulacea tends to colonize muddy estuarine waters and unstable environments (Wesselmann et al, 2021). The limited information available on the provision of ecosystem functions of H. stipulacea in the Mediterranean Sea indicates a similar carbon storage capacity of H. stipulacea and native seagrasses in the eastern Mediterranean (Wesselmann et al, 2021), although carbon stocks in that region ranks among the lowest across seagrass meadows (Fourqurean et al, 2012;Duarte et al, 2013;Mazarrasa et al, 2017). Besides, the dense and tall canopy of P. oceanica attenuates the waves and its meadows play a key role on coastal protection (Sánchez-González et al, 2011), whereas the provision of this ecosystem service by H. stipulacea, with a canopy few centimeters high (Den Hartog, 1970), is low (Christianen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of macroalgal DNA in deeper (5–10 cm) sediment layers is consistent with evidence that DNA can persist for a long time in sediments (Harrison et al, 2019). Therefore, assessments on current distribution patterns should rely on surface (0–1 cm) sediment samples, while past distribution patterns may be observed from deeper sediment layers (Bálint et al, 2018), particularly when combined with geochemical methods to establish chronologies (del Carmen Gomez Cabrera et al, 2019; Marba et al, 2018; Wesselmann et al, 2021). Dated sediment layers can resolve past climate environments (Jensen, Kuijpers, Koc & Heinemeier, 2004; Georgiadis et al, 2018), which, when coupled with macroalgal eDNA analyses, could allow linking past distribution patterns of macroalgae to past changes in the climate, which may help inform projections of future macroalgae distributions patterns with climate change in the Arctic (Krause‐Jensen & Duarte, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most eDNA studies focus on metabarcoding of animals or land plants (Deiner et al, 2017), while only a few studies have explored the use of eDNA to track the export of macroalgae to the open ocean (Ortega et al, 2019) or the contribution of marine plants and macroalgae to sediment pools or food webs, with various success (del Carmen Gomez Cabrera et al, 2019; Nalley et al, 2021; Ortega et al, 2020; Queirós et al, 2019; Reef et al, 2017). The use of eDNA combined with sediment chronologies would also enable the identification of community changes over time (Bálint et al, 2018), as demonstrated by documented invasion of seagrass species in the Eastern Mediterranean (Wesselmann et al, 2021) and community changes in coral reefs of Australia (del Carmen Gomez Cabrera et al, 2019). Enhancing this approach with eDNA metabarcoding of Arctic macroalgae could provide information about past distribution patterns of macroalgae in the Arctic and how shifting climate regimes may have affected their distribution, as well as providing data for predictions of future responses to climate change.…”
Section: Introductionmentioning
confidence: 99%